2022
DOI: 10.1177/15588661221077692
|View full text |Cite
|
Sign up to set email alerts
|

A Data-Driven Approach for Facility Use Definitions in Campus Recreation

Abstract: Existing research in campus recreation establishes a relationship between facility use and academic outcomes, but published studies define users differently. In response to inconsistent definitions of participants in campus recreation, this study uses a data-driven approach to compare facility use definitions. Authors illustrate the implications of choosing different participant definitions for relationships between campus recreation and two undergraduate academic outcomes, first-year retention and first-year … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Future researchers may want to consider recruiting larger samples, or samples that comprise students from multiple institutions. Researchers could also measure physical activity using accelerometers (Slootmaker et al, 2009) and campus recreation facility use via swipe card data (Zegre et al, 2022). Longitudinal research, that continues into and beyond students' first year of post-secondary education is also worth considering.…”
Section: Discussionmentioning
confidence: 99%
“…Future researchers may want to consider recruiting larger samples, or samples that comprise students from multiple institutions. Researchers could also measure physical activity using accelerometers (Slootmaker et al, 2009) and campus recreation facility use via swipe card data (Zegre et al, 2022). Longitudinal research, that continues into and beyond students' first year of post-secondary education is also worth considering.…”
Section: Discussionmentioning
confidence: 99%
“…A study found by this review (Standish & Umbach, 2019) highlighted this measurement issues as they found a nonresponse bias when they comparing both subjective and objective collected data for campus recreation facility usage, sport participation (i.e., intramural or club) and grade point average. Scholars have identified this and have started to refine issues with measuring facility usage (Zegre et al, 2022), however additional work should be conducted to address measurement issues.…”
Section: Discussionmentioning
confidence: 99%
“…However, within this body of literature, some constructs were not always measured through consistent methods of data collection and some scholars did not use established scales. To measure grade point average and campus recreation participation, for example, scholars have used cross sectional surveys (e.g., Mayers et al, 2017) or obtained secondary data from the campus recreation software or institution's office of the registrar (McElveen & Rossow, 2014;Zegre et al, 2022). Using different measures to study the same construct can strengthen the findings of a particular body of work (Newman et al, 2013), however, it can also negatively affect the validity and reliability of the body of literature that has concentrated a particular construct (Babbie, 2020).…”
Section: Discussionmentioning
confidence: 99%